2010
DOI: 10.1021/ar900286y
|View full text |Cite
|
Sign up to set email alerts
|

Systems Analysis of Protein Modification and Cellular Responses Induced by Electrophile Stress

Abstract: Biological electrophiles result from oxidative metabolism of exogenous compounds or endogenous cellular constituents, and they contribute to pathophysiologies such as toxicity and carcinogenicity. The chemical toxicology of electrophiles is dominated by covalent addition to intracellular nucleophiles. Reaction with DNA leads to the production of adducts that block replication or induce mutations. The chemistry and biology of electrophile−DNA reactions have been extensively studied, providing in many cases a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
237
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(244 citation statements)
references
References 44 publications
1
237
0
4
Order By: Relevance
“…They are highly electrophilic and can induce protein dysfunction, DNA damage and apoptosis. 31,32 AKR1B10 can efficiently detoxify the cellular carbonyls and their glutathione conjugates by reducing the reactive carbonyl groups into less active hydroxyls. 6 Therefore, AKR1B10 may protect host cells from carbonyl lesions, promoting cell growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…They are highly electrophilic and can induce protein dysfunction, DNA damage and apoptosis. 31,32 AKR1B10 can efficiently detoxify the cellular carbonyls and their glutathione conjugates by reducing the reactive carbonyl groups into less active hydroxyls. 6 Therefore, AKR1B10 may protect host cells from carbonyl lesions, promoting cell growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Hsp90␤ is not inducible by stress, unlike Hsp90␣, whose level increases in cells under stress. It has also been suggested that the modification of Hsp90 and other chaperones by electrophiles leads to heat shock gene expression (27). The microarray data indeed revealed a dramatic increase in the heat shockregulated transcripts in 6-HITC-treated rat liver RL34 cells.…”
Section: Induction Of Heat Shock Response Via Protein Thiocarbamoylatmentioning
confidence: 78%
“…In some of these studies, endogenous lipid electrophiles, typically generated under inflammatory conditions, have been used as models due to their broad reactivity towards nucleophiles and the availability of detection methods [13,42]. Also, coexistence of inflammatory conditions may potentiate the toxic effects of drugs or reduce the threshold at which they can induce adverse effects.…”
Section: Interactions With Inflammationmentioning
confidence: 99%
“…Whereas these techniques are useful to visualize adducts and to identify the modified proteins, for instance by peptide mass fingerprinting, they usually do not provide information on the site of modification and/or structure of the adducts. Other labeling strategies include "click technology" that uses azido and alkenyl derivatives of electrophilic compounds for subsequent adduct derivatization and detection [12,13], or synthesis of isotopically labeled derivatives recognizable by MS. In cellular and in vitro model systems, drugs or their metabolites can be labeled to facilitate the detection, enrichment and/or identification of adducts.…”
Section: Introductionmentioning
confidence: 99%